The Transformation of the Role of the Office of Religious Affairs (KUA): From Administrative Function to the Front Guard in Preventing Child Marriage in Jambi Province - Hesti Desmira (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2026)
Child marriage in Jambi Province remains a significant issue despite the increase in the minimum age for marriage through Law Number 16 of 2019. This phenomenon indicates a gap between formal regulations and implementation at the grassroots level, requiring deeper policy intervention. This policy article aims to formulate a strategy for transforming the role of the Office of Religious Affairs (KUA) so that it is no longer trapped in the administrative function of marriage registration, but instead becomes a front-line institution in systematic preventive action against child marriage. This paper uses a qualitative methodology with a qualitative approach using descriptive-analytical methods. Data collection was conducted through a literature review of current regulations, population statistics reports in Jambi, and a document review regarding the effectiveness of premarital counseling. The analysis was conducted using a gap analysis framework to map the differences between the legal mandate after the law revision and the current institutional capacity of the KUA in conducting early detection. The analysis shows that the main obstacles to transforming the role of the KUA include limited authority in mitigating marriage dispensations, the lack of competence of religious leaders in psychosocial counseling, and strong sociocultural pressures in the field. This article recommends revitalizing the function of the Office of Religious Affairs (KUA) through the development of an Early Detection System (SDD) for child marriage, increasing the capacity of registrars as certified counselors, and strengthening cross-sectoral collaboration.